Demographic Characterization of Uveal Melanoma Population in Portugal - Geada, Sara (2023)
INTRODUCTION: Uveal melanoma (UM) is the most common intraocular tumor and although rare, remains a clinical challenge for ocular oncologists. Therapeutic options have evolved throughout the years, focusing in eye-conserving modalities. However, long-term survival remains unchanged. Advances in early diagnosis and treatment represent a step forward in improving patients’ outcomes and survival. The purpose of this study is to characterize demographically and clinically the Portuguese population with uveal melanoma evaluated at the National Reference Centre (NRC). METHODS: Prospective, observational study of patients consecutively diagnosed with UM at the Portuguese NRC, between January 2016 and December 2021. Data was collected regarding tumor characteristics, staging (American Joint Committee on Cancer – AJCC), demographic assessment, treatment modality, local control, patient survival and distant metastasis. RESULTS: A total of 215 patients (53% female) were included. The mean age at diagnosis was 61.5± 14.0 years, with symptoms at presentation reported by 75.6%. Choroidal location was the most frequent (83.3%), followed by ciliary body (10.2%), iridociliary (3.3%) and iris (1.4%). The AJCC stage IIA and IIB were the most common at presentation (33.0% and 32.6%, respectively); stage IIIC was the less observed (n=3). Mean baseline basal diameter and thickness were, respectively, 11.7± 3.7 and 6.9±3.4 mm. Primary treatment comprised brachytherapy (n=152, 70.7%), enucleation (n=50, 23.3%), proton beam radiation (n=8, 3.7%) and tumor resection (n=5, 2.3%; only for iris tumors). Mean disease-specific survival (DSS) was 45.8 months (95%CI: 44.5-47.1 months), with a cumulative survival of 89.4 months (95%CI: 83.1-95.7) at 4 years. Mean distant metastases free survival (DMFS) was 53.4 months (95% CI: 50.8-56.0 months), with a cumulative survival of 83.9 months (95% CI: 76.7-91) at 4 years. Higher AJCC stages at presentation, enucleation and increased tumor thickness were associated with lower DSS and DMFS rates. CONCLUSION: This is the first characterization of the Portuguese Population diagnosed with UM in the NRC. Our results highlight the importance of an early diagnosis given that almost 25% of patients were enucleated primarily and were not candidates for globe-sparing treatments. Lower AJCC stages and decreased tumor thickness at the time of diagnosis correlated with better DSS and DMFS, emphasizing the advantages of early treatment.